(untitled) (Bulletin of the International Association for Paleodontology, 2021)
The study of Palatal rugae to determine a person’s identification is known as palatal rugoscopy. The scientific basis of the Palatal rugae analysis is the distinctive and individualistic pattern as a human identifier. According to the Interpol DVI guide, Palatal rugae can be a secondary identifier because it provides supportive information in individual identification. Various studies of Palatal rugae have been conducted to explore its application in sex determination. The purpose of this research was to see if of the Palatal rugae pattern could be used to help with sex determination in the Tengger population, Indonesia. This is a cross-sectional study with a total number of 70 subjects. All subjects from the Tengger area have voluntarily participated in this study. Each participant had a maxillary dental cast made, and the Palatal rugae pattern was examined using Thomas and Kotze’s categorization. The independent sample t-test in SPSS version 20.0 was used for the statistical study. The present investigation found a significant difference between boys and females in the circular pattern of Palatal rugae (p< 0.05). The appearance of the circular pattern showed a statistically significant difference in males and females. The circular pattern was only found and became a characteristic of males in the Tengger population. This study can conclude that the Palatal rugae pattern shows potential as an aid for sex determination in the Tengger population, Indonesia.